The Impact of Using Android-Based Radio Media on Students' Interpersonal Communication Skills and Digital Citizenship Competencies - Anggraeni, Wulan; Wangid, Muhammad Nur (Jurnal Pendidikan Indonesia, 2025)
Interpersonal communication and digital citizenship competencies are currently highly needed by students, along with the widespread use of the internet in society, in responding to various issues. This study aimed to analyze the impact of using Android-based radio media on interpersonal communication, digital citizenship competencies, and the correlation between the two competencies. This research method used a quasi-experiment involving 250 vocational high school students by dividing them into two groups. The experimental group received intervention using Android-based radio media, while the second group used traditional teaching methods. Data analysis used in this study was simple linear regression analysis, t-test, Pearson correlation analysis, and multiple regression. The results showed that using Android-based radio media effectively improved interpersonal communication competencies (ICC) and digital citizenship. In addition, the results showed that 10 ICC skills (self-disclosure, empathy, social relaxation, assertiveness, altercentrism, interaction management, expressivity, support, closeness, and environmental control) positively predicted digital citizenship. Among the skills learned, environmental control and closeness were the strongest predictors of digital citizenship. The implications of the research show that the use of digital radio media integrated into Android devices has great potential to improve the quality of learning that is contextual, interactive, and relevant to current developments.